Contributing role of mitochondrial energy metabolism on platelet adhesion, activation and thrombus formation under blood flow conditions. (3rd October 2022) - Tamura, Noriko; Goto, Shinichi; Yokota, Hideo; Goto, Shinya
Abstract: Platelets have an active energy metabolism mediated by mitochondria. However, the role of mitochondria in platelet adhesion, activation, and thrombus formation under blood flow conditions remains to be elucidated. Blood specimens were obtained from healthy adult volunteers. The consumption of glucose molecules by platelets was measured after 24 hours. Platelet adhesion, activation, and thrombus formation on collagen fibrils and immobilized von Willebrand factor (VWF) at a wall shear rate of 1, 500 s −1 were detected by fluorescence microscopy with an ultrafast laser confocal unit in the presence or absence of mitochondrial functional inhibitors of carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP), antimycin A, and oligomycin. Consumption of glucose molecules within the first 24 h of 4.21 × 10 −15  ± 4.46 x 10 −15 (n = 6) increased to 13.82 × 10 −15  ± 3.46 x 10 −15 (n = 4) in the presence of FCCP, 12.11 × 10 −15  ± 2.33 x 10 −15 (n = 4) in the presence of antimycin A, and 11.87 × 10 −15  ± 3.56 x 10 −15 (n = 4) in the presence of oligomycin (p < .05). These mitochondrial functional blockers did not influence both surface area coverage by platelets and the 3-dimensional size of platelet thrombi formed on the collagen fibrils. However, a rapid increase in the intracellular calcium ion concentration ([Ca 2+ ] i ) upon adhering on immobilized VWF decreased significantly from 405.5 ± 86.2 nM in control to 198.0 ± 79.2 nM in the presence of FCCP (p < .005). A similar decrease in the rapid increase in ([Ca 2+ ] i ) was observed in the presence of antimycin A and oligomycin. Mitochondrial function is necessary for platelet activation represented by a rapid increase in [Ca 2+ ] i after platelet adhesion on VWF. However, the influence could not be detected as changes in platelet adhesion or 3-dimensional growth of platelet thrombi on collagen fibrils.